Antibiogram and Biofilm Production of Escherichia coli Isolated from Water Sewage Plants in Baghdad City - Merdaw, Maysoon A.; Kareem, Amal A. (Iraqi Journal of Science, 2025)
The objective of this study is to investigate and determine the prevalence of antimicrobial-resistant E. coli in wastewater, before and after treatment, and the prevalence of E. coli strains capable of producing biofilms. Nineteen E. coli isolates were isolated from the inputs and outputs samples of AL-Rustamiya Sewage Treatment Plant on AL-Rusafa side (STP1) and the old AL-Karkh STP on AL-Karkh side (STP2). Antimicrobial susceptibility was assessed using VITEK-2, and isolates' ability to form biofilm was evaluated. According to the resistance level of STP1 and STP2, multiple drug resistance (MDR) was found 100% and 75% ,respectively,  of output isolates. Extensive Drug Resistance (XDR) was found in STP1 (possible 2 isolates) more than in STP2 (one isolate). Biofilm formation analysis revealed two strong biofilm-producing isolates in the input samples of STP1, but the output samples showed its elimination and rising in the moderate type. The STP2 output samples revealed increasing in weak biofilm and decreasing in other types. Additionally, Shiga-like toxin–producing types of E. coli (E.coli O157:H7) were found frequently in STP2 than in STP1.